2017
DOI: 10.1097/pas.0000000000000786
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic Shifts in Primary Cutaneous γδ T-Cell Lymphoma Suggest Antigenic Modulation

Abstract: Primary cutaneous γδ T-cell lymphoma (PCGD TCL), an aggressive type of lymphoma, accounts for approximately 1% of all primary cutaneous lymphomas. We have occasionally observed changes in T-cell antigen expression (immunophenotypic [IP] shift) over time, a phenomenon that is considered rare in T-cell lymphoma including cutaneous T-cell lymphoma. Therefore, we assessed sequential biopsies of PCGD TCL for possible IP shifts of the lymphoma cells. We searched for cases of PCGD TCL with consecutive biopsies to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Many cases with IS were treated with multiple agents before the switch was documented on relapse. The most common IS reported in MF (13/15 cases) is a switch from a CD4‐positive/CD8‐negative profile without cytotoxic proteins to a CD4‐negative/CD8‐positive or CD4‐negative/CD8‐negative profile with expression of the cytotoxic markers TIA‐1 and granzyme B 1,3‐13 . Eighteen of 28 patients expired.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many cases with IS were treated with multiple agents before the switch was documented on relapse. The most common IS reported in MF (13/15 cases) is a switch from a CD4‐positive/CD8‐negative profile without cytotoxic proteins to a CD4‐negative/CD8‐positive or CD4‐negative/CD8‐negative profile with expression of the cytotoxic markers TIA‐1 and granzyme B 1,3‐13 . Eighteen of 28 patients expired.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen of 28 patients expired. The average progression time from diagnosis of IS to death is 22 months with a range of (1‐76 months) 1,3‐14 . Notably, Merrill et al described 20 patients with a gamma delta phenotype and noted that CD8 expression appeared to change over time in two patients and CD30 changed over time in four patients, but detailed clinicopathologic information is not available for these cases 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, several authors have identified some cases with a more protracted clinical course, MF-like clinical lesions, and epidermotropism. 182,183 Those cases are negative for CD56 and have expression of CD4 or CD8. It is believed that those cases may have a more indolent behavior compared with the classic forms of PCGDTCL.…”
Section: Cutaneous T-cell Lymphomasmentioning
confidence: 99%